Co-operative motivation: a useful management tool in developing countries - Norman Kemp; Victor Hilliard (Acta Academica)
Having a motivated employee corps is important. In chis article three motivational oriencacions are examined: co-operative, competitive and individualistic approaches. Literature study reveals strong support for a co-operative motivational orientation. Furthermore, chapter 3 of the Constitution of the Republic of South Africa makes provision for co-operative government and administration. The role of co-operationnin the workplace is thus examined, along with the benefits resulting from havingnpeople work together co-operatively. The deleterious effects of competition are alson highlighted in order co strengthen the case for co-operation.